Exploring the barriers and facilitators to health research with children and young people who are looked after - Hannah Dale; Lorna Watson (Scottish Journal of Residential Child Care)
Service provision for children and young people who are looked after should be evidence based, as far as possible, in order to improve their health and wellbeing. This evidence base comes from literature and research. Yet research with young people who are looked after is scarce despite their poor outcomes (For example, Dale and Watson, 2010). This paper provides some reflections on the research process of a health needs assessment in Fife, in which the experience and views of young people was critical (Dale, 2009). It will explore some of the barriers and facilitators in research relevant to health, and makes a plea for a more facilitative approach, within the existing regulatory systems.